2015
DOI: 10.1007/s00345-015-1646-9
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D and prostate cancer prognosis: a Mendelian randomization study

Abstract: A causal role of vitamin D status, as reflected by GC rs2282679 genotype, in disease progression and mortality in prostate cancer patients is unlikely.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 26 publications
0
10
0
Order By: Relevance
“…A detailed description has been published previously [1315]. Briefly, PROCAGENE is a prospective study aimed at investigating genetic risk factors, functional relationships between genetic variations and clinical phenotypes, the genetically modified response to radiotherapy (radiogenomics), and the prognostic importance of genetic markers such as genetic variants in regulators of DNA repair, cell cycle, and apoptosis, including BCL2 -938C>A genotypes [1621].…”
Section: Methodsmentioning
confidence: 99%
“…A detailed description has been published previously [1315]. Briefly, PROCAGENE is a prospective study aimed at investigating genetic risk factors, functional relationships between genetic variations and clinical phenotypes, the genetically modified response to radiotherapy (radiogenomics), and the prognostic importance of genetic markers such as genetic variants in regulators of DNA repair, cell cycle, and apoptosis, including BCL2 -938C>A genotypes [1621].…”
Section: Methodsmentioning
confidence: 99%
“…The Austrian Prostate Cancer Genetics (PROCAGENE) study included 702 prostate cancer patients who were recruited between January 2004 and January 2007. A detailed description has been published previously 24 26 . Briefly, PROCAGENE is a prospective study aimed to investigate genetic risk factors, functional relationships between genetic variations and clinical phenotypes, genetically modified response to radiotherapy (radiogenomics), and the prognostic importance of genetic markers 27 30 .…”
Section: Methodsmentioning
confidence: 99%
“…Follow-up examinations were performed in regular intervals at the Department of Therapeutic Radiology and Oncology 26 . The primary study endpoint was overall mortality.…”
Section: Methodsmentioning
confidence: 99%
“…Discrepancies in the investigated cohorts' characteristics, such as age, BMI, baseline vitamin D status, the dosage of serum vitamin D levels in pre and post diagnosis phase or in different stages of the disease, as well as the presence or absence of adjustment for potential confounding factors, might contribute to inconsistency among studies and to a challenging interpretation of data. However, recent findings demonstrated that isoforms of VDR [98], vitamin D-metabolizing genes [99,100] and DBP [6,101] may be associated with prostate cancer risks or clinical outcomes. The inconsistent findings on the role of vitamin D in prostate cancer can be explained by the interference of insulin like growth factor (IGF) axis components, notoriously involved in prostate cancer etiology and progression [102], which may compromise the antiproliferative vitamin D action.…”
Section: Vitamin D and Cancer: Epidemiological Evidencementioning
confidence: 99%